Metabolic and hormonal changes after laparoscopic sleeve gastrectomy in pediatric population: An observational study - Alghamdi, Hashim; Asiri, Ashwag; Alzahrani, Faris; Alamri, Zainab; AbdelQadir, Yossef Hassan; Shah, Jaffer (Frontiers in Surgery, 2022)
Introduction: Despite the growing popularity of laparoscopic sleeve gastrectomy (SG) for managing severe obesity in children, adolescents, and adults, there is a paucity of studies reporting the effects of SG on metabolic and hormonal outcomes in pediatric populations. Methodology: In this single-centre, retrospective study, we assessed nutritional biomarkers (hemoglobin, ferritin, iron profile, Vitamin B12, Vitamin D, and calcium), glucose homeostasis indicators (C-peptide, HbA1C, and random blood glucose), blood lipids (triglycerides and cholesterol components), hormones involved in the hypothalamic-pituitary-adrenal axis (cortisol and adrenocorticotropic hormone), and thyroid hormones (T3, T4, thyroid-stimulating hormone, and parathyroid hormone) preoperatively and 12-month after SG in children aged 5-15 years. Results: This study included 64 adolescents (mean age = 11.2±2.3 years) who underwent laparoscopic SG. Significant reduction in circulatory C-peptide (-62.1%; p=0.005), HbA1C (-10.9%; p=0.001), random blood glucose (-15.4%; p=0.036), and triglycerides (-39.4%; p=0.003) were observed postoperatively at 12 months compared to baseline. Although we did not observe any changes in cortisol levels, adrenocorticotropic hormone levels declined significantly by -40.9% postoperatively (p=0.033). However, cholesterol components, thyroid hormones, and nutritional biomarkers remained unchanged from baseline. Conclusions: Consistent with prior literature, our study demonstrates improvement or resolution of diabetes and hypertriglyceridemia in the year following SG. However, given that blood cholesterol components, nutritional biomarkers, and thyroid profiles remained unchanged warrants long-term monitoring of nutritional, metabolic, and endocrine factors in adolescents undergoing laparoscopic SG. To the best of our knowledge, this is the first study reporting the effects of SG on thyroid and hypothalamic-pituitary-adrenal axis hormones in pediatric populations.